Evolutionary Algorithm Assisted Optimal Placement of FACTS Controllers in Power System - Saranjeet (My University, 2009)
With the increasing size of power system, there is a thrust on finding the solution to maximize the utilization of existing system and to provide adequate voltage support. For this the flexibility of power is needed. Flexible AC transmission system (FACTS) if placed optimally can be effective in providing voltage support, controlling power flow and in turn resulting into lower losses. The algorithm to find the optimal location of TCSC and STATCOM based on genetic algorithm has been developed. The effect of these devices on line flows and bus voltage profile has been studied by placing at random location and placing them optimally with optimal ratings dictated by genetic algorithm. The effectiveness of developed algorithm has been tested on 5-bus and 30-bus systems.
Keywords: Evolutionary Algorithm; STATCOM; TCSC; Power Flow Analysis; Optimal Alocation